Construction of a macrophage-related prognostic signature and assessment of immune checkpoint inhibitor efficacy of HCC - Shouge Zang; Hongwei Chen; Yuqian Han; Di Cui; Jiangtao Yu (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death, with limited treatment options and high recurrence rates. Prognostic biomarkers and predictors of immune checkpoint inhibitor (ICI) response are urgently needed. This study aimed to develop a macrophage-related gene signature to predict patient outcomes and ICI efficacy, with a focus on the functional role of PLAUR. Single-cell RNA sequencing of paired HCC and normal liver tissues was used to identify macrophage subtypes. A prognostic gene signature was constructed based on macrophage-related genes and validated using the TCGA-LIHC cohort. TIDE analysis was performed to assess ICI response prediction. PLAUR-related cell communication was evaluated using CellChat. Functional assays were conducted to assess the effect of PLAUR knockdown on macrophage polarization, tumor cell behavior, and PI3K/AKT/mTOR pathway activity. Tissue microarray immunofluorescence validated PLAUR expression in situ. An eight-gene macrophage-related signature showed strong prognostic and predictive value. High-risk patients had poorer survival and reduced ICI responsiveness. PLAUR was overexpressed in tumor-associated macrophages and correlated with enhanced cell communication in tumors. Knockdown of PLAUR inhibited M2 polarization, reduced tumor cell proliferation and migration, and suppressed PI3K/AKT/mTOR signaling. In vivo, PLAUR silencing significantly reduced tumor growth in a THP-1/SKHep1 co-injection model. We identified a novel macrophage-related gene signature with clinical utility in HCC. PLAUR promotes immunosuppressive polarization and tumor progression via the PI3K/AKT/mTOR pathway, representing a potential therapeutic target and biomarker for immunotherapy response.